Administration of antibiotics in combination. The antibacterial activity of blood serum and urine after a simultaneous administration of aminoglycosides and ampicillin - Janovská, D; Výmola, F; Godová, T (Journal of hygiene, epidemiology, microbiology, and immunology, 1984)
Blood serum and urine samples collected from a group of volunteers treated with single doses of ampicillin and aminoglycoside preparations given separately or in combination were tested for their antimicrobial activity against the reference strains Staphylococcus aureus SZK 76/69 and ATCC 6538, Pseudomonas aeruginosa SZK 444 and SZK 385, and Escherichia coli SZK 326/71. Out of all antimicrobials and their combinations tested the most powerful was the combination of netilmicin with ampicillin. Of the therapeutic combinations used nowadays in clinical practice the combined use of gentamicin and ampicillin proved also effective. These antibiotic combinations appear thus to be best suited for the treatment of mixed Pseudomonas aeruginosa and Staphylococcus aureus infections and of urinary tract infections caused by bacterial strains exhibiting in the in vitro susceptibility assays a reduced sensitivity to some of the antibiotic preparations used.
Keywords: dospělí; kombinovaná farmakoterapie; Humans; Drug Therapy, Combination; Bacteria; Staphylococcus aureus; Netilmicin; antibakteriální látky; netilmicin; gentamiciny; mužské pohlaví; Adult; ampicilin; Kanamycin; Ampicillin; ženské pohlaví; Gentamicins; lidé; Anti-Bacterial Agents; Pseudomonas aeruginosa; kanamycin; Male; Female